ANALISIS KADAR FLAVANOID TOTAL MENGGUNAKAN SPEKTROFOTOMETRI UV-VIS DALAM KULIT BUAH SALAK (Salacca zalacca V.) - Adam Mustapa,M.Sc, Mohammad; Taupik, Muhammad; Ramadhan L, Aditya (State University of Gorontalo, 2019)
The Snake Fruit (Salacca zalacca (Gaertn.) Voss) skin is considered as a waste, but there are a small number of people who use this fruit skin as an medicine. A compound that plays a role in snake fruit skin for the treatment is flavonoid. The purpose of this study was to determine the level of flavonoid contained in the extract of snake fruit skin. The method used to determine the amount of flavonoid compound contained in it is the UV-Vis Spectrophotometry method. The result of reading the absorbance value of each snake fruit fraction obtained from the methanol fraction was 0.568 and ethyl acetate fraction of 0.319, which were then calculated by using the quercetin linear equation standard, y = 0.0608 x -0.0188 with the correlation coefficient (R2) = 0.997. The result obtained for each snake fruit fraction for flavonoid level in the methanol fraction was 96.51 g/mL and in ethyl acetate fraction was 55.56 g/mL.